2007
DOI: 10.1103/physrevd.75.023520
|View full text |Cite
|
Sign up to set email alerts
|

Realizing scale-invariant density perturbations in low-energy effective string theory

Abstract: We discuss the realization of inflation and resulting cosmological perturbations in the low-energy effective string theory. In order to obtain nearly scale-invariant spectra of density perturbations and a suppressed tensor-to-scalar ratio, it is generally necessary that the dilaton field φ is effectively decoupled from gravity together with the existence of a slowly varying dilaton potential. We also study the effect of second-order corrections to the tree-level action which are the sum of a Gauss-Bonnet term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 79 publications
1
47
0
Order By: Relevance
“…If β = 0 and 0 < γ < 1, it was shown that the tensor perturbations suffer from instabilities on small scales, because c 2 T = 2γ − 5 is negative [10]. This type of instabilities has been also found in Refs.…”
Section: Power-law Inflationmentioning
confidence: 61%
See 3 more Smart Citations
“…If β = 0 and 0 < γ < 1, it was shown that the tensor perturbations suffer from instabilities on small scales, because c 2 T = 2γ − 5 is negative [10]. This type of instabilities has been also found in Refs.…”
Section: Power-law Inflationmentioning
confidence: 61%
“…In the case β = 0 (no potential), we choose ω = −1 and γ = γ − , since γ + > 1. The condition for inflation requires α < 1/4 [10]. Taking the positive sign of φ, we obtain…”
Section: Power-law Inflationmentioning
confidence: 99%
See 2 more Smart Citations
“…The model buildings of inflation in string theory has been widely investigated, e.g., [11][12][13][14] and [15,16] for recent reviews. The inflationary GWs is a powerful tool to probe the physics beyond GR, since it is only affected by the physics relevant to gravity, e.g., the change of the propagating speed of GWs [17].…”
Section: Jhep02(2016)059mentioning
confidence: 99%